STRATEGIES FOR FOSTERING RELIGIOUS UNDERSTANDING AT MUALAF CENTER SIMALUNGUN - Ramadhani, Gita; Nurhanifah (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
This study aims to find out the strategy for fostering Islamic religious understanding for converts carried out by the Simalungun Conversion Center. This research uses a qualitative approach with field study methods through observation, interviews, and documentation. The results of the study show that coaching is carried out through a worship practice approach, the Tsaqifa method in learning the Qur'an, the use of digital media and personal communication, and the provision of socio-economic support. These strategies have proven to be effective in improving converts' understanding of Islam, the ability to read the Qur'an, the discipline of worship, and the sustainability of religious education. This study concludes that a comprehensive and contextual coaching approach plays a role in shaping the Islamic personality of converts as a whole, although there are still challenges such as low learning motivation, time constraints, and institutions that are not optimal